Spectroscopic Optical Coherence Tomography by Using Multiple Multipole Expansion - Hon Luen Seck; Ying Zhang (Photonics, 2018)
This paper presents a pre-processing method to remove multiple scattering artifacts in spectroscopic optical coherence tomography (SOCT) using time–frequency analysis approaches. The method uses a multiple multipole expansion approach to model the light fields in SOCT. It is shown that the multiple scattered fields can be characterized by higher order terms of the multiple multipole expansion. Hence, the multiple scattering artifact can thus be eliminated by applying the time–frequency transform on the SOCT measurements characterized by the lower order terms. Simulation and experimental results are presented to show the effectiveness of the proposed pre-processing method.